An engineering geomorphological investigation of hillslope stability in the Peak District of Derbyshire - Cross, Martin (1987)
Large-scale civil engineering works, planning and land-management in areas known to have a landslide problem require regional landslide susceptibility evaluation. The Matrix Assessment Approach (MAP) is introduced as a technique for establishing an index of slope stability over large areas. The method allows the relative landslide susceptibility to be computed over large areas using a discrete combination of geological/geomorphological parameters. MAP was applied to a region in the Peak District, Derbyshire. The model identified key geological/geomorphological parameters involved in deep-seated failures, provided an effective means of classifying the stability of slopes over a large area and successfully indicated sites of previously unmapped landslides. The resultant regional landslide susceptibility index provides useful preliminary information for use at the pre-site/reconnaissance stages, of large-scale civil engineering works such as highway construction.